Effects of α‐Thalassemia on HbA1c Measurement. Issue 6 (17th May 2016) - Xu, Anping; Ji, Ling; Chen, Weidong; Xia, Yong; Zhou, Yu
Abstract : Background: α‐Thalassemia is a benign condition that is often present in patients with diabetes mellitus. Here, we evaluated the effects of different genotypes α‐thalassemia on HbA1c measurement. Methods: A total of 189 samples from nondiabetic patients were analyzed. HbA1c analysis was performed by ion‐exchange high‐performance liquid chromatography, boronate affinity HPLC, immunoassay, and capillary electrophoresis. Fasting glucose, fructosamin, and HbA2 were also performed. All samples were confirmed by genotyping for thalassemia. Results: In patients with two or three functional α‐genes, HbA1c values were not significantly different from those of controls ( P > 0.05); however, in individuals with α‐thalassemia with one functional α‐gene (i.e., HbH disease), HbA1c levels were significantly different from those of controls ( P < 0.01). HbA1c values were significantly lower in individuals with HbH disease than in control individuals and patients in the other two α‐thalassemia groups. For patients with HbH disease, there were no significant differences in the four HbA1c measurement systems ( P > 0.05). Conclusions: In this study, HbA1c values in samples from individuals with two or three functional α‐genes basically reflected the normal mean blood glucose level, while those in samples from individuals with one functional α‐gene did not.